Controversies in Severe Traumatic Brain Injury Management (Springer International Publishing, 2018)
This book addresses the current levels of evidence for management of a variety of critical parameters after severe traumatic brain injury (TBI), as well as providing the reader with practical approaches to care based upon existing evidence. As the management of severe traumatic brain injury remains one of the most complicated and controversial areas of neurosurgery, trauma care and critical care medicine, it will serve as a helpful reference and guide to the impact of potential therapeutic interventions. Each chapter is organized by the proposal of a commonly encountered clinical question, addressing the current evidence for a variety of treatments, outlining the relevant questions on the topic that have not been adequately addressed in the literature, summarizing the options for treatment and the level of evidence upon which each is based, and finally proposing questions yet to be addressed in the literature. The text identifies ongoing questions for future research relevant to the topic at hand as well as providing a comprehensive educational reference for resident and fellowship training. Controversies in Severe Traumatic Brain Injury Management will become an invaluable resource and data point for neurosurgeons, neurointensivists, trauma surgeons and other healthcare professionals involved in the care and treatment of TBI patients.